Impact of Statutes of Limitations in Arbitration Cases - Rakan Abdullah Alshaeri; Emad Mohammad Yousuf Jan (International Journal of Law Research and Studies, 2026)
Arbitration has become a comprehensive legal system for settling disputes between parties, and its importance lies in combining the requirements of justice with the wishes of the disputing parties, especially in light of the complexity of traditional judicial procedures.The statute of limitations for a lawsuit is the expiration of a legally defined and known period of time since the creation of a right without it being claimed judicially, which leads to its dismissal in filing a lawsuit. These rules aim to ensure the stability of legal positions and prevent disputes from remaining pending.The Kingdom of Saudi Arabia, in light of Vision 2030, has enacted legislation to regulate the life of society and the individual, both socially and economically, especially with the issuance of the Civil Transactions Law dated (1444 AH), and what was stated in its Article No. (295), which stipulated that the right does not expire with the passage of time, but the claim against the denier is not heard after the expiry of ten years, as the concept of prescription and its effect on rights moved from the realm of judicial interpretation to the realm of disciplined regulation, to become a tool to ensure the stability of legal positions and prevent the accumulation of historical disputes.During my study, demonstrated the link between the concept of arbitration as an agreement to settle disputes between parties, and the idea of ​​prescription as a legal effect and a necessity for the stability of commercial and financial transactions.To illustrate this, I highlighted the nature of arbitration, its types, the justification for resorting to it, its nature, effect, and validity, in addition to defining prescription, its types, the difference between acquisitive prescription and extinctive prescription, and what is the period of prescription that prevents hearing the parties to the lawsuit in the Saudi Civil Transactions System.
Keywords: Arbitration System; Statute of Limitations; Substantive and Procedural Rules; Saudi Civil Transactions System